DEEP LEARNING-BASED SOCIAL STUDIES CURRICULUM ANALYSIS IN PREPARING STUDENTS IN THE INDUSTRIAL ERA 5.0 - Siswadi; erni sulistiawati; Hasan Triyakfi; Tutuk Ningsih (SOSIOEDUKASI, 2026)
This study aims to analyze the relevance of a Social Studies curriculum based on deep learning in preparing students to face the challenges of the Industry 5.0 era. The study employs a qualitative research design based on a literature review by examining recent scholarly works on deep learning pedagogy, Social Studies curriculum development, and competencies required in the Industry 5.0 era. Data were collected from academic journals, books, and policy reports published within the last five years and were subsequently analyzed using content analysis to identify key themes related to curriculum innovation, student competencies, and instructional strategies. The findings indicate that the integration of deep learning in Social Studies learning can enhance students’ critical literacy, collaboration skills, digital awareness, and social responsibility. Project-based learning, inquiry-based activities, and technology-supported instruction provide meaningful and contextual learning experiences by connecting social knowledge with real-life issues. However, this study also identifies several challenges in implementation, including limited teacher readiness, unequal access to digital infrastructure, and the need for systematic professional development. In conclusion, a deep learning–based Social Studies curriculum is highly relevant for preparing students to become adaptive, ethical, and socially responsible citizens in the Industry 5.0 era, although its successful implementation requires curriculum redesign, enhancement of teacher capacity, and adequate educational policy support to ensure an equitable and sustainable transformation of Social Studies education.